Nutrient adequacy and diet quality in a Mediterranean population with metabolic syndrome: A cross-sectional study. Issue 3 (March 2020) - Bibiloni, Maria del Mar; Bouzas, Cristina; Abbate, Manuela; Martínez-González, Miguel A.; Corella, Dolores; Salas-Salvadó, Jordi; Zomeño, M. Dolors; Vioque, Jesús; Romaguera, Dora; Martínez, J. Alfredo; Wärnberg, Julia; López-Miranda, José; et al.
Summary: Background & aims: Few studies have compared micronutrient intake and fulfilment of average requirements (EAR) in non-diabetic, pre-diabetic and diabetic adults at high cardiovascular risk. We assessed these variables in a large sample of participants in the PREDIMED-PLUS randomized trial of primary cardiovascular prevention with diet and physical activity. Design: Baseline assessment of nutritional adequacy in n = 5792 men and women, aged 55–75 years, with overweight/obesity and some metabolic syndrome features. Methods: Participants were categorised as non-diabetic ( n = 2390), pre-diabetic ( n = 1322) or diabetic ( n = 2080) by standard criteria. Food and nutrient intake were assessed using a validated food frequency questionnaire. Micronutrients examined were vitamins B1, B2, B3, B6, B12, A, C, D, E and folic acid; Ca, K, P, Mg, Fe, Se, Cr, Zn, and iodine. The proportion of micronutrient inadequacy was evaluated using the EAR or adequate intake (AI) cut-offs. Diet quality was also determined using a 17-item energy-restricted Mediterranean diet (MedDiet) questionnaire. Results: Compared to non-diabetic participants, those with pre-diabetes had lower intakes of total carbohydrates (CHO) and higher intakes of total fat and saturated fatty acids (SFA) and were more likely to be below EAR for folic, while diabetic participants had lower intakes of total CHO and higher intakes of protein, total fat, monounsaturated fatty acids, SFA and cholesterol and were less likely to be below EAR for vitamins B2, and B6, Ca, Zn and iodine. Diabetic participants disclosed higher adherence to the MedDiet than the other two groups. Conclusions: Older Mediterranean individuals with metabolic syndrome and diabetes had better nutrient adequacy and adherence to the MedDiet than those with pre-diabetes or no diabetes.